2017
DOI: 10.1103/physrevlett.119.208005
|View full text |Cite
|
Sign up to set email alerts
|

Forced Imbibition in Porous Media: A Fourfold Scenario

Abstract: We establish a comprehensive description of the patterns formed when a wetting liquid displaces a viscous fluid confined in a porous medium. Building on model microfluidic experiments, we evidence four imbibition scenarios all yielding different large-scale morphologies. Combining high-resolution imaging and confocal microscopy, we show that they originate from two liquid-entrainment transitions and a Rayleigh-Plateau instability at the pore scale. Finally, we demonstrate and explain the long-time coarsening o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
58
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(60 citation statements)
references
References 28 publications
2
58
0
Order By: Relevance
“…Figure c clearly shows that Δ S w is significantly smaller for Ca < Ca c (Δ S w ≤ 0.08) than for Ca > Ca c . Odier et al () performed flow rate‐controlled imbibition experiments in microfluidics and showed that the increased oil saturation after breakthrough is Δ S w ≤ 0.075 in capillary regime (supporting information Figure S8), which is consistent with our results shown in Figure c. From the water‐flooding experiments in water‐wet sandstone, Dullien et al () reported that at capillary imbibition, there is no more oil production after water breakthrough, supporting our results in Figure g.…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…Figure c clearly shows that Δ S w is significantly smaller for Ca < Ca c (Δ S w ≤ 0.08) than for Ca > Ca c . Odier et al () performed flow rate‐controlled imbibition experiments in microfluidics and showed that the increased oil saturation after breakthrough is Δ S w ≤ 0.075 in capillary regime (supporting information Figure S8), which is consistent with our results shown in Figure c. From the water‐flooding experiments in water‐wet sandstone, Dullien et al () reported that at capillary imbibition, there is no more oil production after water breakthrough, supporting our results in Figure g.…”
Section: Resultssupporting
confidence: 90%
“…In capillary imbibition, studies on pore-scale events, including Haines jump (Haines, 1930), corner flow (Dong & Chatzis, 1995), and snap off (Roof, 1970), have shown that the pore-scale mechanisms not only impact the displacement patterns and efficiency (Chen, Guo, et al, 2018;Hu et al, 2018;Odier et al, 2017) but also contribute to the macroscopic hydraulic properties at the Darcy scale (Niessner et al, 2011). For capillary-viscous regime in imbibition, these local displacement events would be suppressed as viscous forces increasingly dominate the displacement processes (Odier et al, 2017;Zhao et al, 2016). Therefore, identification of the transition is fundamental to the description of forced imbibition.…”
Section: 1029/2018gl079302mentioning
confidence: 99%
See 1 more Smart Citation
“…While the gap-averaged two-dimensional approach has been very successful and insightful in describing important nonlinear features of the hydrodynamics of multiphase flows [41,43,[100][101][102][103][104][105][106], it has some limitations. In particular, it cannot resolve the formation of fluid wedges at corners for strongly wetting systems [107][108][109][110][111][112], which exert an important control on the hydraulic continuity of the liquid phase [113,114] and therefore on evaporation rates [115]. Our model can be extended to three dimensions, where the hydrodynamics in the bulk fluid are described by the Navier-Stokes equations.…”
Section: Discussionmentioning
confidence: 99%
“…A model network of pores was built inside a microfluidic chip, allowing direct observation of the phenomena occurring during oil recovery. 214,215 However, to our knowledge such a method has not been transposed to the study of transport inside the pores of catalyst particles yet.…”
Section: Perspectives For Fundamental Understandingmentioning
confidence: 99%